Investigating Gender-based violence against internally displaced women in Debre Berhan, Central Ethiopia: A mixed-methods study using the socio-ecological framework - Kindie Mitiku; Sisay Shiwasinad; Solomon Shiferaw (PLoS ONE, 2025)
Background Gender-based violence (GBV) is a major health problem affecting displaced populations disproportionately. However, limited research existed on the prevalence, barriers, and facilitators for survivors seeking care. Objective This study aims to estimate the prevalence of GBV and investigate the barriers and facilitators influencing survivors’ access to care. Methods A mixed-methods cross-sectional study was conducted in 2024 involving 1,863 women. Women were recruited through random sampling. The qualitative component included five NGO workers and eleven GBV survivors, who were selected purposively. Quantitative data were collected using the Assessment Screen to Identify Survivors Toolkit. The qualitative data were analysed thematically with Atlas Ti 8, guided by the socio-ecological framework. Results Nearly one-third (31%) of women experienced GBV, with 25.2% of them facing it in the past year. The most common types of violence were threats of violence (32.1%), physical violence (25.8%), forced marriage (19.1%), and sexual violence (10.0%). Nearly 80% of GBV incidents took place in IDP camps, mainly perpetrated by intimate partners and family members. Barriers to seeking GBV services at the individual level included self-isolation, reluctance to disclose survivor status, and lack of awareness. Community-level restrictions comprised social stigma, gossip, and inadequate social support, while institutional challenges involved budget constraints and a lack of confidentiality. Structural barriers included camp overcrowding, insecurity, and mistrust in the justice system. Self-efficacy acted as an individual-level enabler for survivors to seek care. Enablers at the institutional level included support from NGOs, access to secure housing, and availability of a one-stop centre. Access to community-based GBV workers was viewed as a crucial community-level facilitator for survivors seeking care. Conclusions GBV is widespread among internally displaced women, particularly in camps. Despite the presence of some facilitators, GBV survivors encounter numerous barriers at all levels of the socio-ecological framework. Overcoming these barriers requires comprehensive and coordinated efforts. Key strategies include increasing awareness of the available GBV services, reducing community stigma, building supportive networks, safeguarding survivors’ privacy, decreasing overcrowding in camps, enhancing security measures, and rebuilding trust in justice systems.